THE PESANTREN WAY IN CREATING LEADERS - Novianti, Lelly Lailiyah; Wijoyo, Suparto; Rahmah, Mas; Thalib, Prawita; Salman, Radian; Ristawati, Rosa; Fauzia, Ficky Dahliana (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
Pesantren or Islamic traditional boarding school is one the unique institution within Indonesian Islam. Serving a comprehensive education with emphasis on the internalization of Islamic values is the main purpose of pesantren. Additionally, since they also serve the society safeguarding and leadership, Pesantren promote the emergence of new leadership. This study explores how pesantren cultivates leadership by integrating spiritual depth with intellectual rigor highlighting 5 pesantrens across East Java. Using a Systematic Literature Review (SLR) from Scopus, WoS, and Semantic Scholar, the findings identify five leadership development categories in pesantren: moral and character-based, entrepreneurial, humanist and inclusive, spiritual and religious, and transformational and innovative leadership. As a result, Pesantren provides a strong foundation for leadership education, grounded in moral, spiritual, and local wisdom. This model has been proven effective in shaping character, integrity, and responsibility, making it a relevant framework for fostering the nation's moral and leadership development. Their alumni show strong leadership skills that beneficial for their role in society.